Surgical efficacy of bone grafts and GTR on endodontic microsurgery: An overview of bone regeneration technology applied in magnification (Research, Society and Development, 2024)
Surgical endodontic procedures have been performed for over a century with new modifications in the primary technique. When traditional endodontic therapy and retreatment fail and the periapical infection persists, surgical intervention to remove the apical biofilm is recommended with an attempt to preserve the dental element. The newest breakdowns by researchers and dental surgeons are obtaining new techniques of the Guided Tissue Regeneration associated with periradicular surgery. This article presented an integrative review of a series of reported cases and vigorous analyses, expressing the results of endodontic microsurgery and GTR association. This review study aims to present clearly and concisely, encompassing complex studies and published analyses to collect the advantages and the efficacy of the use of bone grafts inserted in periradicular microsurgery. During the execution of this research to elaborate an integrative review, the previous data selection was conducted using methodological strategies to simplify and filter the substantial content inserted inside the proscript study. 86 bibliographic articles from the following databases: PubMed, Scielo, Journal of Endodontics, Science Direct, Wiley Online Library, Google Scholar, and Virtual Health Library were analyzed. Moreover, 70,9% of the studies analyzed weren't compatible with the research purpose and 29,1% were included. The principles of bone regeneration being inserted in apical lesion recovery have shown to be promising, and future studies are being encouraged to be developed to further improve applicability in surgical endodontics.